Pembangunan sistem bajet ladang untuk LKPP Corp. Sdn. Bhd. yang teragih, pelbagai aras dan pelbagai perusahaan - Kasim, Shahreen (2005)
The development of estate budget for LKPP Corp. Sdn. Bhd. (LCSB) which is distributed, multilevel and multienterprise is build to make this company manage its budget more easier. Budget is a financial statement which can control financial of institutional, organizational or personal account. This allocation is needed to run activities and productivities in the whole year. Before the implementation of this system, LCSB prepared budget manually. Therefore, this system is build to provide an automation budget system. Throughout the development of this system, the author has done a research in all estate under LCSB. The deployment of this system will manage to help the management team to produce yearly budget to distribute to all estate under its area. This system also manage to produce reports that could help to prepare the budget. This system is using the open source technology and applying the web development metodology